(untitled) (Revista LIDER, 2020)
This study analyzes mobile populations in Nicaragua in the context of Central American integration. The analysis reveals an emphasis on security in policies rather than a human rights approach. Likewise, the analysis suggests that the structural problems of the Central American states have impeded an integral policy of development and migration.